A person-centered approach to achievement goal orientations in competitive tennis players: Associations with motivation and mental toughness - Richard Gregory Cowden; Nicolas Mascret; Timothy Ryan Duckett (Elsevier, 2021)
Background: Research on achievement goal orientations in sport has typically relied on the use of variable-centered approaches that tend to overlook population heterogeneity. In this study, we used a person-centered approach to identify subgroups of competitive tennis players according to unique combinations of achievement goal orientations and tested for subgroup differences in motivation and mental toughness. Methods: A sample of 323 competitive tennis athletes (69.35% male) between 15 and 25 years of age (17.60 ± 2.40 years, mean ± SD) completed the 3 × 2 Achievement Goal Questionnaire for Sport, Sport Motivation Scale II, and Mental Toughness Index. Latent profile analysis was used to identify unique combinations of achievement goal orientations. Comparisons between latent subgroups on autonomous motivation, controlled motivation, and mental toughness were performed using analysis of variance. Results: Latent profile analysis supported 3 distinct patterns of achievement goal profiles that were primarily distinguishable based on valence of competence (i.e., approach vs. avoidance). Analyses of variance indicated that athletes who were classified into subgroups that endorsed approach types of goals (regardless of the types of avoidance goals they endorsed) reported higher levels of autonomous motivation and mental toughness. Conclusion: Results indicated that athletes tend to pursue a number of achievement goals collectively rather than in isolation. Although approach goals are more commonly linked to adaptive psychological functioning and positive outcomes, avoidance goals may also be associated with desirable psychological characteristics if they are pursued in conjunction with approach types of achievement goals.